HUBUNGAN ANTARA ETOS KERJA, MOTIVASI, SIKAP INOVATIF DAN PRODUKTIVITAS USAHATANI (Studi Kasus Pada Usahatani Padi Sawah di Kecamatan Tumpaan Kabupaten Minahasa Selatan) - Vicky R. B. Moniaga (Sam Ratulangi University, 2012)
This study aims to (a) describe these three psychological factors and productivity of rice farming, and (b) to study whether there is a significant relationship between these psychological factors (work ethic, achievement motivation and innovative attitude) with farm productivity. Based on the analysis of descriptions of the main variables of the study, then through the method of